1999
DOI: 10.1021/bi991769v
|View full text |Cite
|
Sign up to set email alerts
|

Using Phosphorothioate-Substituted RNA To Investigate the Thermodynamic Role of Phosphates in a Sequence Specific RNA−Protein Complex

Abstract: Part of the binding affinity and specificity in RNA-protein complexes is often contributed by contacts between the protein and backbone phosphates that are held in position by the RNA structure. This study focuses on the well-characterized interaction between a dimer of the MS2 coat protein and a small RNA hairpin. Using a short oligoribonucleotide which contains all the necessary sequence elements required for tight protein binding, a single phosphorothioate linkage was introduced at 13 different positions. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 56 publications
2
40
1
Order By: Relevance
“…The effects of phosphorothioate modification on RNAprotein interaction match direct structural information obtained from corresponding X-ray structures or that derived by cryoelectron microscopy very well+ For example, results obtained with the MS2 coat protein-RNA (Milligan & Uhlenbeck, 1989;Dertinger et al+, 2000) and tRNA-synthetase systems (Schatz et al+, 1991;Rudinger et al+, 1992;Voertler et al+, 1998) are directly comparable to interactions seen in three-dimensional crystal structures of the complexes+ Phosphorothioated tRNAs bound by the ribosome give specific cleavage patterns that are characteristic for the particular ribosomal binding site (Dabrowski et al+, 1995) and that are dependent on the functional state of the ribosome (Dabrowski et al+, 1998)+ The protection pattern observed with P-site bound peptidyl-tRNA analogs was in perfect agreement with the ribosome contacts seen with an f-Met-tRNA at the ribosomal P site in cryoelectron microscopy pictures (Malhotra et al+, 1998)+ Recently, we selected a short fragment of domain I of 23S rRNA (GG295-343CC, 53 nt) that binds independently and simultaneously the ribosomal proteins L4 and L24 (Stelzl et al+, 2000a(Stelzl et al+, , 2000b, two key proteins for the early assembly of the large subunit of bacterial ribosomes (Nierhaus, 1991)+ L24 is one of the two assembly initiator proteins of the 50S subunit (Nowotny & Nierhaus, 1982), and L4 is essential for the formation of the first assembly intermediate particle (Spillmann et al+, 1977)+ Here, we present phosphorothioate probing data of the ternary L24-rRNA-L4 complex determined by an in-gel analysis and compare them with that of the two binary complexes L24-rRNA and rRNA-L4+ In-gel iodine cleavage enables the probing of RNA structures in homogeneous populations of the different complexes, thereby overcoming the problem that a preparation of a ternary complex still contains a fraction of binary complexes obscuring the signals+ The results demonstrate that the rRNA region within the binary complexes adopts a conformation that is different from that observed in the ternary complex+ We discuss these probing data in light of the recent crystallographically determined three-dimensional model of the 50S ribosomal subunit (Ban et al+, 2000)+…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…The effects of phosphorothioate modification on RNAprotein interaction match direct structural information obtained from corresponding X-ray structures or that derived by cryoelectron microscopy very well+ For example, results obtained with the MS2 coat protein-RNA (Milligan & Uhlenbeck, 1989;Dertinger et al+, 2000) and tRNA-synthetase systems (Schatz et al+, 1991;Rudinger et al+, 1992;Voertler et al+, 1998) are directly comparable to interactions seen in three-dimensional crystal structures of the complexes+ Phosphorothioated tRNAs bound by the ribosome give specific cleavage patterns that are characteristic for the particular ribosomal binding site (Dabrowski et al+, 1995) and that are dependent on the functional state of the ribosome (Dabrowski et al+, 1998)+ The protection pattern observed with P-site bound peptidyl-tRNA analogs was in perfect agreement with the ribosome contacts seen with an f-Met-tRNA at the ribosomal P site in cryoelectron microscopy pictures (Malhotra et al+, 1998)+ Recently, we selected a short fragment of domain I of 23S rRNA (GG295-343CC, 53 nt) that binds independently and simultaneously the ribosomal proteins L4 and L24 (Stelzl et al+, 2000a(Stelzl et al+, , 2000b, two key proteins for the early assembly of the large subunit of bacterial ribosomes (Nierhaus, 1991)+ L24 is one of the two assembly initiator proteins of the 50S subunit (Nowotny & Nierhaus, 1982), and L4 is essential for the formation of the first assembly intermediate particle (Spillmann et al+, 1977)+ Here, we present phosphorothioate probing data of the ternary L24-rRNA-L4 complex determined by an in-gel analysis and compare them with that of the two binary complexes L24-rRNA and rRNA-L4+ In-gel iodine cleavage enables the probing of RNA structures in homogeneous populations of the different complexes, thereby overcoming the problem that a preparation of a ternary complex still contains a fraction of binary complexes obscuring the signals+ The results demonstrate that the rRNA region within the binary complexes adopts a conformation that is different from that observed in the ternary complex+ We discuss these probing data in light of the recent crystallographically determined three-dimensional model of the 50S ribosomal subunit (Ban et al+, 2000)+…”
Section: Introductionmentioning
confidence: 60%
“…The tentative primary binding site of L24 is the region G298-G301 and C337-G338 (Fig+ 2C, green nucleotides) as inferred from our previous selection studies (Stelzl et al+, 2000a)+ This conclusion is substantiated by the in-gel phosphorothioate probing data+ (1) Phosphorothioate modification of nt A299, G301, and C302 interferes with the L24 binding+ (2) L24 protects the RNA backbone at G298 and A300 from reaction with iodine; the O-to-S substitution at A300 favors binding+ (3) In the 39 part of RNA L4 , an interesting effect is seen with the phosphorothioated G338 that interferes with binding, whereas the minor bound fraction is exposed to iodine cleavage in the L24 complex+ The signals of C334-C337, which cannot be resolved for every base in some experiments, is protected in the L24-rRNA complex+ (4) A G298U transversion that increases the affinity of protein L4 to the rRNA fragment abolishes L24 binding (Stelzl et al+, 2000a)+ Interestingly, only the L24 protections of G298, A300, C334-C337, and A340 and the L4 protection at A320 are similar in the binary and the ternary complexes+ All the other signals change qualitatively when we compare the binary complexes with the ternary complex (Fig+ 2)+ Striking differences between binary and ternary complexes are seen+ (1) Twelve O-to-S substitutions are enriched in the ternary complex, but only two of these (A300 and A320) were enriched in the binary complexes (Fig+ 2D; e+g+, U321, C323, A324)+ Although phosphorothioates are known to increase the affinity for a protein in some cases, the structural meaning is not clear+ It could be that sulfur reduces electrostatic repulsion of the oxygen atoms in the RNA backbone if the molecule is packed tightly, because the R P -sulfur renders the corresponding S P -oxygen less negative (Dertinger et al+, 2000)+ (2) In the loops of helices 19 and 20 some signals from the binary complexes disappear (e+g+, G311, A332), new signals are observed (e+g+, U306, A330) and some signals change (e+g+, A309, G313)+ (3) Striking changes are even observed in the protein interaction sites: At the L24 binding site the interferences are either lost (e+g+, G301, C302; Fig+ 2D) or replaced by protection signals (G297, A299, G338)+ The phosphorothioate 59 to U321 that abolishes L4 binding to the RNA becomes protected and, most astonishingly, is now enriched in the ternary complex+ (4) Apparently conflicting results are found in the binary complexes for two positions in the L4 binding region: An A320 modification that is enriched in the rRNA L4 -L4 binary complex but interferes with L24-rRNA L4 complex formation is also enriched in the ternary complex+ The opposite case is seen with thioated A322, which gives an interference signal in the binary complex with L4 and is enriched in that with L24+ In the ternary complex the interference effect is seen; as with L4 alone, thioated A322 also impedes ternary complex formation+ These observations demonstrate an RNA conformational change when going from one of the binary complexes to the ternary complex+…”
Section: Cleavage Patterns Of the Rrna L4 Fragment Under Various Condmentioning
confidence: 99%
“…The formation of hydrogen bonds between the phosphate backbone and the protein has been shown to be an important determinant of binding affinity (Dertinger et al 2000;Dertinger and Uhlenbeck 2001). In most of the cases where we have structural information, movement of phosphate atoms does not disrupt such hydrogen bonding, although the bond lengths are altered, presumably with implications for binding free energy.…”
Section: The F5/2ap10 Complex: Implications For Modeling and Probing mentioning
confidence: 99%
“…Modification-interference analysis of complex between protein L1 and L1-7 rC:dC RNA+ A: Autoradiogram of total and selected L1-7 rC:dC RNA after partial alkaline hydrolysis and separation on a 15% polyacrylamide gel as described in Materials and Methods+ The positions of C residues are indicated+ Total: unfractionated L1-7 rC:dC RNA; selected: L1-7 rC:dC RNA selected by protein L1 (Mg 2ϩ only)+ U 2 : reference lane showing the products that result when the same RNA is partially digested with RNase U 2 + B: Histogram shows the relative intensities of individual nucleotide bands resulting from partial alkaline hydrolysis of L1-7 rC:dC RNA selected by protein L1+ Band intensities were calculated using phosphorImager measurements from at least three independent experiments+ The radioactivity of each band in the selected RNA lane was divided by the radioactivity of the corresponding band in the total RNA lane+ The average value of these ratios was then normalized to 1+0 and each value adjusted accordingly+ A value of 1 indicates no interference+ carried out by a modification of the phosphorothioate alkylation reaction using iodine as a cleavage agent (Gish & Eckstein, 1988)+ Iodine is ideally suited for this purpose as it is uncharged and reasonably small, it reacts rapidly with phosphorothioates and its presence does not interfere with the electrophoretic migration of RNA fragments in a gel+ In the experiments involving L1-4 rU:rUaS and L1-7 rC:rCaS RNAs, a reduction in the intensity of the bands corresponding to position 2122 was detected in the L1-bound fractions+ For L1-4 rA:rAaS and L1-7 rG:rGaS RNAs, a similar reduction in intensity was observed at position 2176+ These results led us to conclude that substitution of Rp oxygens in the phosphate groups preceding positions 2122 and 2176 with sulfur disrupts L1-23S rRNA interaction and confirm that the effects of these modifications on binding are not base specific+ Manganese rescue experiments revealed that the presence of Mn 2ϩ during the selection process partially restores the ability of the RNAs containing Rp sulfur in the phosphate bonds preceding nt 2122 and 2176 to bind L1+ Nonbridging phosphoryl oxygens can contact ligands directly via hydrogen bonds and electrostatic contacts (Dertinger et al+, 2000), or indirectly via divalent metal ion coordination (e+g+, Christian & Yarus, 1993;Chanfreau & Jacquier, 1994;Harris & Pace, 1995;Knöll et al+, 1997;Sood et al+, 1998)+ In the latter case, reversal of the effects of phosphorothioate substitution by manga- Histogram shows the relative intensities of individual nucleotide bands resulting from partial alkaline hydrolysis of L1-4 rU:dT RNA selected by protein L1+ Band intensities were calculated as described in the legend to Figure 5+ nese is indicative of the coordination of divalent metal ions by specific phosphate groups in the RNA+ This conclusion is based on the fact that Mg 2ϩ has a much stronger affinity for oxygen than sulfur (.3 ϫ 10 4 -fold in ATPbS), whereas the difference in the affinity of Mn 2ϩ for oxygen and sulfur is much smaller (,200-fold) (Pecoraro et al+, 1984)+ Although manganese ions may not bind to the RNA backbone in exactly the same way as magnesium ions, the positions of divalent metal-ionbinding sites inferred from manganese rescue experiments have been confirmed by X-ray crystallography in several instances (e+g+, Pley et al+, ...…”
Section: Discussionmentioning
confidence: 83%